2021
DOI: 10.1038/s41398-021-01703-1
|View full text |Cite
|
Sign up to set email alerts
|

Opposing white matter microstructure abnormalities in 22q11.2 deletion and duplication carriers

Abstract: Deletions and duplications at the 22q11.2 locus are associated with significant neurodevelopmental and psychiatric morbidity. Previous diffusion-weighted magnetic resonance imaging (MRI) studies in 22q11.2 deletion carriers (22q-del) found nonspecific white matter (WM) abnormalities, characterized by higher fractional anisotropy. Here, utilizing novel imaging and processing methods that allow separation of signal contribution from different tissue properties, we investigate whether higher anisotropy is driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 116 publications
(148 reference statements)
1
4
0
Order By: Relevance
“…Notably, our study revealed that the covariation of GMV exhibited distinct directions of effect between individuals with 22q11DS and controls across various SBPs. This finding aligns with recent research, particularly from the ENIGMA 22q11.2 Working Group, which has employed diverse methodologies to investigate cortical and subcortical structure (Ching et al, 2020; Sun et al, 2020), as well as white matter microstructure in 22q11DS (Seitz‐Holland et al, 2021; Villalón‐Reina et al, 2020). Specifically, Villalón‐Reina et al found that fractional anisotropy (FA) of the white matter exhibited two distinct directions of effect in 22q11DS individuals relative to demographically matched control subjects: elevated FA in 22q11DS individuals relative to controls was observed in callosal and projection fibers (i.e., internal capsule and corona radiata), while decreased FA in 22q11DS individuals was observed in certain association fibers (Villalón‐Reina et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Notably, our study revealed that the covariation of GMV exhibited distinct directions of effect between individuals with 22q11DS and controls across various SBPs. This finding aligns with recent research, particularly from the ENIGMA 22q11.2 Working Group, which has employed diverse methodologies to investigate cortical and subcortical structure (Ching et al, 2020; Sun et al, 2020), as well as white matter microstructure in 22q11DS (Seitz‐Holland et al, 2021; Villalón‐Reina et al, 2020). Specifically, Villalón‐Reina et al found that fractional anisotropy (FA) of the white matter exhibited two distinct directions of effect in 22q11DS individuals relative to demographically matched control subjects: elevated FA in 22q11DS individuals relative to controls was observed in callosal and projection fibers (i.e., internal capsule and corona radiata), while decreased FA in 22q11DS individuals was observed in certain association fibers (Villalón‐Reina et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Carriers of the 22q11.2 deletion with psychosis showed overall lower AD, RD, and MD compared with 22q11.2 deletions without psychosis. A recent study found opposite effects in DTI measures in 22q11.2 deletion and duplication carriers (higher FA in deletion and lower FA in duplication) (42). Using advanced DTI methods, the authors found that increased FA in deletion carriers was accompanied by higher fractions of primary and secondary fiber populations (F1 and F2, reflecting dominant and nondominant fiber orientation, respectively) and lower extracellular space and was associated with enlarged cerebrospinal fluid volume and reduced white matter volume.…”
Section: Diffusion-weighted Imaging Findings On Individual Cnv Cohortsmentioning
confidence: 93%
“…The underlying mechanism of FA changes in CNV carriers is unclear. The most recent DTI study on 22q11.2 associates higher FA in deletion carriers with volumetric changes (42). Similar studies in other CNVs are needed, although substantial research is still needed to confidently relate DTI data to underlying cellular changes (59).…”
Section: Convergence In Neurodevelopmental Cnvsmentioning
confidence: 94%
“…The method of Free-Water Imaging [47] overcomes some of those obstacles, as it allows the quantifying of the extracellular free water fractional volume (FW), which is more sensitive and biologically specific [48]. Several studies have applied the method to study psychosis, including individuals at risk for psychosis [49][50][51][52], early onset psychosis [53], first episode psychosis [54,55], and chronic psychosis [56][57][58]. In large-scale cross-sectional and longitudinal studies, we demonstrated an FW increase in white and gray matter in individuals with early phase psychosis [53,[59][60][61].…”
Section: Introductionmentioning
confidence: 99%